1995
DOI: 10.1136/bmj.310.6979.560
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of risk factors for development of non-insulin dependent diabetes in middle aged British men

Abstract: Objective-To determine the risk factors for noninsulin dependent diabetes in a cohort representative ofmiddle aged British men.Design-Prospective study. Subjects and setting-7735 men aged 40-59, drawn from one group practice in each of 24 towns in Britain. Known and probable cases of diabetes at screening (n= 158) were excluded.Main outcome measures-Non-insulin dependent diabetes (doctor diagnosed) over a mean follow up period of 12 8 years.Results-There were 194 new cases of non-insulin dependent diabetes. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
297
5
14

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(347 citation statements)
references
References 23 publications
31
297
5
14
Order By: Relevance
“…Further results from the Nurses Health Study suggested that, independently of exercise levels, sedentary behaviours, especially TV watching, were associated with significantly elevated risk of type 2 diabetes and obesity, whereas even light to moderate activities were associated with a substantially lower risk [24]. Also, an inverse association between exercise and incidence of type 2 diabetes was observed among residents of the UK [21,25] and Finland [13,26]. The findings in the present study extend the literature showing that leisure time physical activity is associated with a reduction in risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Further results from the Nurses Health Study suggested that, independently of exercise levels, sedentary behaviours, especially TV watching, were associated with significantly elevated risk of type 2 diabetes and obesity, whereas even light to moderate activities were associated with a substantially lower risk [24]. Also, an inverse association between exercise and incidence of type 2 diabetes was observed among residents of the UK [21,25] and Finland [13,26]. The findings in the present study extend the literature showing that leisure time physical activity is associated with a reduction in risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Undoubtedly, various issues interlink with each other in a complicated and, at present, rather undetermined manner, to produce an overall picture of lower awareness and self-help in the South Asian population. Although genetic effects may play a role in the higher prevalence of diabetes in the Asian population, 25 lifestyle issues such as exercise are also very important 26,27 and sedentary lifestyles may place Asians in the high-risk category. 28,29 Although information to promote increased physical activity and control obesity has been promoted by health information systems, this study highlights a lack of understanding of these important issues in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Although cigarette smoking is positively associated with hyperinsulinism and insulin resistance in some studies 39,40 , the association between tobacco and gestational diabetes mellitus has been little investigated. A cross-sectional study carried out in Scandinavia 41 showed that to smoke more than ten cigarettes per day during pregnancy affects the homeostasis of the glucose towards gestational diabetes mellitus, which was confirmed by others 42 .…”
Section: Cigarette Smokingmentioning
confidence: 99%